A genome-wide association study of a rage-related misophonia symptom and the genetic link with audiological traits, psychiatric disorders, and personality - Smit, Dirk J. A.; Bakker, Melissa; Abdellaoui, Abdel; Hoetink, Alexander E.; Vulink, Nienke; Denys, Damiaan (Frontiers in Neuroscience, 2023)
People with misophonia experience strong negative emotional responses to sounds and associated stimuli—mostly human produced—to an extent that it may cause impairment in social functioning. The exact nature of the disorder remains a matter of ongoing research and debate. Here, we investigated the genetic aetiology of misophonia to understand contributing genetic factors and shed light on individual differences in characteristics that are related to the disorder. For misophonia, we used an unpublished genome-wide association study (GWAS) from genetic service provider 23andMe, Inc., on a self-report item probing a single common misophonic symptom: the occurrence of rage when others produce eating sounds. First, we used gene-based and functional annotation analyses to explore neurobiological determinants of the rage-related misophonia symptom. Next, we calculated genetic correlations (rG) of this rage-related misophonia symptom GWAS with a wide range of traits and disorders from audiology (tinnitus, hearing performance and hearing trauma), psychiatry, neurology, and personality traits. The rage-related misophonia symptom was significantly correlated with tinnitus, major depression disorder (MDD), post-traumatic stress disorder (PTSD), and generalized anxiety disorder (GAD; 0.12 < rG < 0.22). Stronger genetic correlations (0.21 < rG < 0.42) were observed for two clusters of personality traits: a guilt/neuroticism and an irritability/sensitivity cluster. Our results showed no genetic correlation with attention deficit and hyperactivity disorder, obsessive-compulsive disorder, and psychotic disorders. A negative correlation with autism spectrum disorder (ASD) was found, which may be surprising given the previously reported comorbidities and the sensory sensitivity reported in ASD. Clustering algorithms showed that rage-related misophonia consistently clustered with MDD, generalized anxiety, PTSD and related personality traits. We conclude that — based on the genetics of a common misophonia symptom — misophonia most strongly clusters with psychiatric disorders and specific personality profile consistent with anxiety and PTSD.